2014
DOI: 10.1128/jcm.00738-14
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Simplexa Flu A/B & RSV PCR with Cytospin-Immunofluorescence and Laboratory-Developed TaqMan PCR in Predominantly Adult Hospitalized Patients

Abstract: To compare Simplexa Flu A/B & RSV PCR with cytospin-immunofluorescence and laboratory-developed TaqMan PCR methods, 445 nasopharyngeal samples were tested. Of these, 199 were positive (46 for respiratory syncytial virus [RSV], 120 for influenza A, and 33 for influenza B) and 246 were negative. The direct fluorescent-antibody assay (DFA) detected 132 (66.3%) positive samples, Simplexa direct detected 162 (81.4%), Simplexa using extracts detected 177 (88.9%), and lab-developed TaqMan PCR reference methods detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…As shown in Table 1, the sensitivity of DFA testing can be excellent in pediatric patient populations. However, as seen with first-generation POC testing, the sensitivity of DFA testing is significantly decreased in adult patient populations, especially compared to commercial nucleic acid amplification tests (Table 1) (271). It should be noted that not all molecular assays are equivalent for the detection of respiratory viruses, and our own experience has occasionally identified instances where DFA testing was able to identify RSV while molecular test results were variable (unpublished observations).…”
Section: Direct Fluorescent Antibody Testingmentioning
confidence: 98%
“…As shown in Table 1, the sensitivity of DFA testing can be excellent in pediatric patient populations. However, as seen with first-generation POC testing, the sensitivity of DFA testing is significantly decreased in adult patient populations, especially compared to commercial nucleic acid amplification tests (Table 1) (271). It should be noted that not all molecular assays are equivalent for the detection of respiratory viruses, and our own experience has occasionally identified instances where DFA testing was able to identify RSV while molecular test results were variable (unpublished observations).…”
Section: Direct Fluorescent Antibody Testingmentioning
confidence: 98%
“…It was reported that rapid influenza diagnostic tests showed low and variable sensitivity [ 17 , 18 ] depending on the influenza A subtype [ 19 ], while some FDA-cleared diagnostic tests did not detect the novel H3N2v viruses [ 20 ]. Diagnosis of influenza infection from an unknown risk respiratory specimen involves multiple assays [ 17 , 21 ]. Identification of the first case of A(H5N1) virus infection in North America involved multiple laboratories [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several papers were published on Simplexa™ Flu A/B & RSV, using an extracted nucleic acid and/or direct sample testing and comparing to conventional methods or molecular tests (Alby et al, 2013;Hindiyeh et al, 2013;Selvaraju et al, 2014;Ko et al, 2013;Woodberry MW1 et al, 2013;Landry and Ferguson, 2014;Svensson et al, 2014). In this study, the Simplexa™ Flu A/B & RSV Direct assay system showed comparable performance characteristics for Flu A, Flu B and RSV in comparison with TAC testing.…”
Section: Discussionmentioning
confidence: 71%